2000
DOI: 10.1101/gr.10.8.1103
|View full text |Cite
|
Sign up to set email alerts
|

Gene Survey of the Pathogenic Protozoan Trypanosoma cruzi

Abstract: We have performed a survey of the active genes in the important human pathogen Trypanosoma cruzi by analyzing 5013 expressed sequence tags (ESTs) generated from a normalized epimastigote cDNA library. Clustering of all sequences resulted in 771 clusters, comprising 54% of the ESTs. In total, the ESTs corresponded to 3054 transcripts that might represent one-fourth of the total gene repertoire in T. cruzi. About 33% of the T. cruzi transcripts showed similarity to sequences in the public databases, and a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 21 publications
3
19
0
2
Order By: Relevance
“…1 shows the distribution among eight functional categories of all ESTs to which a putative identity could be assigned using Blast analyses. Similar to the EST distribution obtained in previous EST studies (Verdun et al 1998, Porcel et al 2000, with epimastigote cDNA libraries and Agüero et al 2004, with an amastigote cDNA library), a large fraction of mRNAs encoding components of the translation machinery is found in amastigotes. Because the two amastigote libraries were not normalized, we expected a significant number of cDNAs to correspond to abundant transcripts present in this stage of the parasite.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…1 shows the distribution among eight functional categories of all ESTs to which a putative identity could be assigned using Blast analyses. Similar to the EST distribution obtained in previous EST studies (Verdun et al 1998, Porcel et al 2000, with epimastigote cDNA libraries and Agüero et al 2004, with an amastigote cDNA library), a large fraction of mRNAs encoding components of the translation machinery is found in amastigotes. Because the two amastigote libraries were not normalized, we expected a significant number of cDNAs to correspond to abundant transcripts present in this stage of the parasite.…”
Section: Resultssupporting
confidence: 62%
“…The full list of the identified ESTs and a detailed functional classification can be found at http:/ /www.icb.ufmg.br/~nage/aest/supplemental_table.html The high frequency of ribosomal protein cDNAs (9% of the total number of cDNAs) is in agreement with the results of the amastigote EST survey reported by Agüero et al (2004), who found an even larger percentage (17.4%) of total ESTs generated from the CL Brener amastigote library encoding ribosomal proteins. This proportion is also similar in the data set from the two epimastigote cDNA libraries (Verdun et al 1998, Porcel et al 2000, thus indicating that both forms of T. cruzi depend on the maintenance of the protein synthesis apparatus characteristic of rapidly dividing cells. In line with that, microarray studies of gene expression during trypomastigote (a non-dividing stage) to amastigote differentiation also identified several genes encoding ribosomal proteins as a group of amastigote up-regulated genes (Minning et al 2003).…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…We determined the complete sequence of the T. cruzi cDNA clone TENU4155 (accession number AW324852) (36), which showed similarities to polyprenyl synthases. The sequence surrounding the first ATG complied with the published rules for start codons in protozoa (37).…”
Section: Identification Of T Cruzi Spps-mentioning
confidence: 99%